Relations of cognitive emotion regulation, personality traits and affectivity - Popov, Stanislava (Primenjena psihologija, 2010)
The aim of this study was to define the influence that cognitive strategies of emotion regulation have on general affectivity. Since the affectivity depends primarily on the temperament, that is, on the biologically determined aspects of personality, the personality dimensions are necessarily included in the research of this relationship. The study included 264 participants from general population. Hierarchical regression analyses were used to examine these relationships. The influence of personality traits was much greater in the determination of both affective dimensions; however it was greater in the determination of the negative rather than the positive dimension. Considering the different dimensions of personality, openness to experience was distinguished as a significant predictor in both affectivity dimensions. In negative affectivity, it is predictor in negative direction (ß= -.17, p<.01), and in positive affectivity it has a greater influence than extraversion in positive direction (ß= .29, p< .01). In both cases some strategies of the cognitive emotion regulation were shown to be significantly influential in the determination of both dimensions of the affectivity, that is, their influence should not be neglected. Self-blame is the most significant predictor of the negative affectivity (ß= .14, p<.05), while the positive refocusing is the most significant predictor of the positive affectivity (ß= .11, p< .05)